2016
DOI: 10.3390/ijms17122076
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Oligochitosan Elicitor from Fusarium sambucinum and Its Elicitation of Defensive Responses in Zanthoxylum bungeanum

Abstract: Oligosaccharide elicitors from pathogens have been shown to play major roles in host plant defense responses involving plant–pathogen chemoperception and interaction. In the present study, chitosan and oligochitosan were prepared from pathogen Fusarium sambucinum, and their effects on infection of Zanthoxylum bungeanum stems were investigated. Results showed that oligochitosan inhibited the infection of the pathogen, and that the oligochitosan fraction with a degree of polymerization (DP) between 5 and 6 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 80 publications
(95 reference statements)
2
13
0
Order By: Relevance
“…Very low concentrations (picomolar; pM) of chitin oligomers can still trigger PTI [106]. Chitin oligomers with large degrees of acetylation and polymerisation induce main PTI responses (ROS production and alkalinisation) [107,108,109]. Chitosan induces callose deposition in plants [110].…”
Section: Plant Immunity: Role Of Chitin/chitosanmentioning
confidence: 99%
“…Very low concentrations (picomolar; pM) of chitin oligomers can still trigger PTI [106]. Chitin oligomers with large degrees of acetylation and polymerisation induce main PTI responses (ROS production and alkalinisation) [107,108,109]. Chitosan induces callose deposition in plants [110].…”
Section: Plant Immunity: Role Of Chitin/chitosanmentioning
confidence: 99%
“…It was found that chitosan amendment increased plant phenylalanine ammonia lyase activity, which is the crucial enzyme of phenylpropanoid metabolism, and the subsequent increase in phenolic content, polyphenol oxidase, peroxidase, and chitinase is a general response associated with disease resistance (Anand et al 2009; Mejía-Teniente et al 2013). The use of oligo-chitosan with the degree of polymerisation of five significantly enhanced defensive activities of all four enzymes (Li et al 2016). Chitosan was also found to increase the production of glucanohydrolases, specific phytoalexins with antifungal activity and of lignin-like material and reduced macerating enzymes such as polygalacturonases and pectin methylesterase (Ali et al 2014).…”
Section: Biocontrol and Other Agricultural Applicationsmentioning
confidence: 99%
“…Moreover, chitosan induces proteinase inhibitors (Walker-Simmons and Ryan 1984), phytoalexin biosynthesis (Hadwiger and Beckman 1980) and callose formation (Köhle et al 1985) in dicot species. The plants’ response to chitin, chitosan and the derived oligosaccharides depends on the acetylation degree (Akiyama et al 1995; Cord-Landwehr et al 2016; Li et al 2016) and the degree of polymerisation (Walker-Simmons and Ryan 1984; Li et al 2016). of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharide growth elicitors from various pathogens reported having a critical role in host plant protection mechanism encompassing plant pathogen chemoperception chemoperception and interaction [15].…”
Section: Introductionmentioning
confidence: 99%